2004
DOI: 10.1515/mult.2004.012
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating cross-cultural difference in electronic discussion

Abstract: Although a good deal of research exists both on computer-mediated communication (CMC) and on cross-cultural communication, rarely are the two areas brought together. In practice however, extrapolation from one context to the other is common, with the internet and email being increasingly used to teach cross-cultural communication. What assumptions about the transfer of culture into cyberspace inform these practices? And are these assumptions well-founded? This paper explores practices of discussion on French a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…While scholars like Jackson (2007, p. 154) suggest 'social and cultural norms may reinforce usage', as well as perceptions of such technologies, there remains a dearth of scholarship on individual experiences of those from collectivist cultures with CMC (Yum and Hara 2005). Other scholars have also reported that culture plays a pivotal role in communication and communication styles and may influence, govern and regulate CMC usage (Ting-Toomey 1991, Amant 2002, Hanna and Nooy 2004. To begin to address this gap, this article explores how one racialized group, South Asian youth, make use of CMC in their cross-gender relationships, their motives for doing so, and potential negative consequences of such use.…”
Section: Introductionmentioning
confidence: 99%
“…While scholars like Jackson (2007, p. 154) suggest 'social and cultural norms may reinforce usage', as well as perceptions of such technologies, there remains a dearth of scholarship on individual experiences of those from collectivist cultures with CMC (Yum and Hara 2005). Other scholars have also reported that culture plays a pivotal role in communication and communication styles and may influence, govern and regulate CMC usage (Ting-Toomey 1991, Amant 2002, Hanna and Nooy 2004. To begin to address this gap, this article explores how one racialized group, South Asian youth, make use of CMC in their cross-gender relationships, their motives for doing so, and potential negative consequences of such use.…”
Section: Introductionmentioning
confidence: 99%
“…Hanna and de Nooy are both senior lecturers in French in the University of Queensland, Australia, and have published numerous articles about intercultural computer-mediated communication in the last few years (Hanna & de Nooy, 2003; Hanna & de Nooy, 2004; de Nooy, 2006). Learning Language and Culture via Public Internet Discussion Forums is a continuation of their recent work and concentrates on the cultural practices in French and English speaking forums.…”
mentioning
confidence: 99%
“…Moreover, it has been argued that the online communication strategies adopted by different groups do not necessarily correspond to their cultural norms in other contexts (Hanna & de Nooy, 2004). Some have suggested that rather than being a site for cultural diversity, the Internet is displaying a tendency towards cultural uniformity, either because it is becoming a culture-free environment, or because users of different backgrounds are converging towards one dominant set of behavioral patterns -these patterns being close to American communication patterns, rather than those of any other culture, because of the origins of the Internet and the predominance of Americans among its users.…”
mentioning
confidence: 99%